ENERGI TERBARUKAN DALAM PEMBANGUNAN BERKELANJUTAN - Abubakar Lubis (Jurnal Teknologi Lingkungan, 2007)
Renewable energy is non fossil energy which can be renewed and managed properly. Therefore, the renewable energy resources would be sustainable. Those that can be classified as renewable energy are geothermal, hydro, solar, wind, biomass, ocean, fuel cell, and nuclear.